Bed Separation Characteristics of an LTCC Panel and Subsidence Controlling Grouting: Case Study of Longquan Coal Mine, China. (3rd February 2022) - Zheng, Jun; Zhou, Guoqing; Zhou, Yuliang; Yuan, Dongfeng; Zhao, Tielin
Abstract : The bed separation backfill grouting (BSBG) is commonly used to mitigate the surface subsidence caused by coal mining. The distribution characteristics of bed separation and its dynamic evolving process are crucial for BSBG design. This paper utilizes the continuum-discontinuum element method (CDEM) to study the distribution characteristics of bed separation for a longwall top coal caving (LTCC) panel of Longquan coal mine. Numerical results indicate that in addition to the bed separation below the primary key stratum, several small bed separations may also occurred in the strata between the primary key stratum and the subordinate key stratum. The bed separations in the overburden could be classified into three classes: the upper bed separation, the middle bed separation, and the lower bed separation. The upper bed separation has the longest duration time, and the middle bed separation has the shortest duration time. And the BSBG should be started before the closure of the middle bed separation. Based on the actual geological information, the BSBG scheme for 4203 LTCC panel is proposed to mitigate the surface subsidence by taken the results of numerical simulation into consideration. In addition, the case study of the BSBG is introduced in detail. By using gangue power slurry, BSBG could not only effectively mitigate the surface subsidence but also solve the problems of environmental pollution and land occupation caused by traditional gangue stacking. The present study could provide technical support for surface subsidence mitigation and coal gangue disposal for LTCC mining with similar conditions.